5(1-x)=-5(6x-6)

Simple and best practice solution for 5(1-x)=-5(6x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(1-x)=-5(6x-6) equation:


Simplifying
5(1 + -1x) = -5(6x + -6)
(1 * 5 + -1x * 5) = -5(6x + -6)
(5 + -5x) = -5(6x + -6)

Reorder the terms:
5 + -5x = -5(-6 + 6x)
5 + -5x = (-6 * -5 + 6x * -5)
5 + -5x = (30 + -30x)

Solving
5 + -5x = 30 + -30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30x' to each side of the equation.
5 + -5x + 30x = 30 + -30x + 30x

Combine like terms: -5x + 30x = 25x
5 + 25x = 30 + -30x + 30x

Combine like terms: -30x + 30x = 0
5 + 25x = 30 + 0
5 + 25x = 30

Add '-5' to each side of the equation.
5 + -5 + 25x = 30 + -5

Combine like terms: 5 + -5 = 0
0 + 25x = 30 + -5
25x = 30 + -5

Combine like terms: 30 + -5 = 25
25x = 25

Divide each side by '25'.
x = 1

Simplifying
x = 1

See similar equations:

| 223=6*x+7 | | 12.6=x*40 | | 9(-10+x)-5(2x+9)=4-x+11 | | 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) | | 6a+17=-1 | | -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k | | 24+8x=40 | | X^2+kx-k+8=0 |

Equations solver categories